Coastal Aerial Photo-Laser Survey (CAPS) — A Nearshore Charting System - Crandall, Clifford J. (The International Hydrographic Review, 2015)
The watchwords in the Mapping & Charting world today are “Remote Sensing” . It seems like everything that gathers data is a remote sensor of some kind. Since that is the case, I would like to add another word to our remote sensing vocabulary and that word is “lidargrammetry” or, if you prefer, “hydrogrammetry”. I’m not sure this is the first time either of these words has been used but I hope it is not the last, because it really describes what the Coastal Aerial Photo-laser Survey (CAPS) system is all about. Namely, making measurements from aerial photography — in this case making hydrographic measurements using a lidar system for depth control and photography for area coverage and compilation. (See figure 1). Imagine traversing a survey area at 150 knots and taking precise leadline measurements approximately every 10 metres along your traverse. If you can envision this, you can understand and appreciate the advantages of using an airborne laser depth sounder to provide high speed depth information in nearshore coastal waters. All one has to do then is tie this data all together with stereo photography and with positional information and make a chart. Sounds easy doesn’t it ? Unfortunately, it is not quite so simple. The problems of obtaining a workable CAPS system are numerous.